2022
DOI: 10.1007/s10668-022-02646-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the COVID-19 pandemic prevalence in Africa through optimal feature selection and clustering: evidence from a statistical perspective

Abstract: The COVID-19 pandemic, which outbroke in Wuhan (China) in December 2019, severely hit almost all sectors of activity in the world as a consequence of the restrictive measures imposed. Two years later, Africa still emerges as the least affected continent by the pandemic. This study analyzed COVID-19 prevalence across African countries through country-level variables prior to clustering. Using Spearman-rank correlation, multicollinearity analysis and univariate filtering, 9 country-level variables were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Wrapper methods have gained attention in COVID-19 research as a powerful approach for selecting relevant features and optimizing predictive models. Several studies have explored the application of wrapper methods in the context of COVID-19 analysis [ [40] , [41] , [42] , [43] ]. Researchers have utilized techniques like Recursive Feature Elimination (RFE), Genetic Algorithms (GA), Selection by Filtering (SBF), and Sequential Feature Selection (SFS) to identify factors such as demographic information, comorbidities, and environmental variables that significantly impact COVID-19 outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Wrapper methods have gained attention in COVID-19 research as a powerful approach for selecting relevant features and optimizing predictive models. Several studies have explored the application of wrapper methods in the context of COVID-19 analysis [ [40] , [41] , [42] , [43] ]. Researchers have utilized techniques like Recursive Feature Elimination (RFE), Genetic Algorithms (GA), Selection by Filtering (SBF), and Sequential Feature Selection (SFS) to identify factors such as demographic information, comorbidities, and environmental variables that significantly impact COVID-19 outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have utilized techniques like Recursive Feature Elimination (RFE), Genetic Algorithms (GA), Selection by Filtering (SBF), and Sequential Feature Selection (SFS) to identify factors such as demographic information, comorbidities, and environmental variables that significantly impact COVID-19 outcomes. By selecting the most informative features, these studies aim to enhance the accuracy of predictive models [ 40 , 41 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meteorological conditions can influence how the virus survives and persists within a given environment, which in turn might affect the likelihood of transmission of the disease 12 . Overall, most of the available studies tend to report lower transmission rates at warmer temperatures but higher transmission in colder and dry environments 9 , 13 , along with exacerbating effects of humidity, higher air concentration in fine particles 14 , lower wind speeds 15 or lower solar radiation 9 . For example, in South Asia, Hossain et al 12 identified a positive association between COVID-19 confirmed cases and minimum, maximum and average temperatures, rainfall, relative air humidity, wind speed and surface pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the top five hard-hit countries ( in decreasing order of severity : South Africa, Morocco, Tunisia, Egypt and Libya) reported 60.3% and 69.7% of the total confirmed cases and deaths (respectively) 5 . These figures are thought to be due to specific traits of the African context, including the low rate of urbanization, the limited transport network hindering the mobility of people, and the young age of the population 8 , 9 . Also, the lower case fatality rate in Africa of non-communicable diseases such as cancer, cardiovascular accidents and diabetes (already known as comorbidities in this pandemic) has been often put forward 7 , 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation